2001
DOI: 10.1017/s1014233900001474
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation, conservation and improvement of Sahiwal cattle in India

Abstract: SummaryThe Sahiwal cattle, one of the best dairy breeds of Zebu cattle in India and Pakistan, originate from the Montgomery district of Pakistan and is distributed on farmer herds in certain pockets of the bordering districts of Punjab and Rajsthan in India. The animals of this breed are also available in Kenya and are used for crossing with local East African Zebu types to improve milk production. Sahiwal cattle have deep body, loose skin, short legs, stumpy horns and a broad head with pale red to dark brown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 1 publication
1
13
2
1
Order By: Relevance
“…Whereas, figures reported by Joshi et al (2001) and Sirrajuddin and Rehman (1999) are lower than the current findings of study. The discrepancy between the reports might have been due to environmental conditions prevailing in the area when study was conducted and reported by various authors mentioned above.…”
Section: Dry Periodcontrasting
confidence: 80%
See 2 more Smart Citations
“…Whereas, figures reported by Joshi et al (2001) and Sirrajuddin and Rehman (1999) are lower than the current findings of study. The discrepancy between the reports might have been due to environmental conditions prevailing in the area when study was conducted and reported by various authors mentioned above.…”
Section: Dry Periodcontrasting
confidence: 80%
“…The age at first calving was 1080 days in Zebu cattle ( Joshi et al, 2001) and 1119 days in Red Sindhi cattle (Sheikh and Zelam, 2000), which fall in the range (726.0 -1132 days) of the current study for Red Sindhi cattle. Reported values for age at first calving in Cholustani and Red Sindhi cattle ranges from 999-1174 days (Choudhry et al, 1983;Sheikh and Zelam, 2000;Souza and Usmani, 1990;Joshi et al, 2001) are in close agreement with the current findings for Red Sindhi cattle.…”
Section: Age At First Calvingmentioning
confidence: 39%
See 1 more Smart Citation
“…In earlier studies of Indian native cattle, the major focus was on assessment of morphological parameters and information gained from local sources (Nivsarkar et al 2000;Joshi et al 2001;Singh et al 2002;Gaur et al 2003;Karthickeyan et al 2006). Recently, assessment of genetic diversity and delineation of the genetic structure of cattle breeds have become a major concern, as some of the important populations and breeds are either declining or breed characters are being diluted under the present production system.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, categorization of these cattle breeds has often been based on morphological data and information gained from the local breed keepers. 1,[4][5][6][7] Hence, an effort to deduce the genetic structure among the Indian native cattle breeds becomes pertinent for the development of future management strategies. For this purpose, microsatellites markers previously exploited for diversity studies in cattle populations from Africa, Europe, and Asia [8][9][10][11][12][13][14] are utilized herein to characterize Indian native cattle breeds.…”
mentioning
confidence: 99%